Microplastic Analysis at Sea Water and Sediment in the Mahitam Island Lampung Bay using FT-IR - Nita Sari; Widiastuti, Endang Linirin; Pratami, Gina Dania; Tugiyono, Tugiyono (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2023)
The amount of garbage that accumulates in the waters causes environmental damage which is getting worse. The breakdown of plastic waste into smaller particles that have been degraded is called microplastic. This study aims to analyze the number of particles, shapes, and types of microplastic polymers found in the water and sediments of Mahitam Island. The research location was determined by purposive random sampling with three stations based on plastic sources, namely Station I, Station II, and Station III, which had different characteristics from laboratory-based testing for seawater and sediment. Microplastic analysis on seawater samples was carried out by adding a solution of 70% ethanol, 30% H2O2, and 30% NaCl, and on sediment samples was carried out by adding a solution of FeSO4 (0.05 M), NaCl, and 30% H2O2. The content of the number of particles and the shape of microplastics were analyzed using a microscope, while the analysis of microplastic polymers using FT-IR. The first thing to do is to extract microplastics The forms of microplastic found are Fiber, Film, Fragments, and Pellets. The highest number of microplastic particles was the type of film for water samples at Station 1 and Station 2 for sediment samples. The types of polymers found in water and sediments on Mahitam Island are polyvinyl chloride (PVC), polyethylene (PE), polypropylene (PP), and polystyrene (PS) which come from plastic waste. Microplastics are known to originate from the use of plastic originating from tourist activities and originating from the sea currents of Mahitam Island.